TO THE QUESTION OF HEIDEGGER’S QUESTIONING - Selishcheva, D. V. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2017)
The aim of the article is to show the systematic character of the philosophical views of Martin Heidegger based on an investigation of the main methodological prerequisites of his philosophizing (thinking). Five such preconditions are singled out: the notion of man as a sign without meaning, the idea of modular existence, the use of terms instead of scientific concepts, the conversion and trust of the thinker to poetic images and the astounding essence of thinking. The article proves that the systematic nature of Heidegger’s views allows one to view works of different periods of his work as part of a single philosophical project.